Cranial irradiation alters neuroinflammation and neural proliferation in the pituitary gland and induces late‐onset hormone deficiency. Issue 24 (10th November 2020) - Xu, Yiran; Sun, Yanyan; Zhou, Kai; Xie, Cuicui; Li, Tao; Wang, Yafeng; Zhang, Yaodong; Rodriguez, Juan; Zhang, Xiaoan; Shao, Ruijin; Wang, Xiaoyang; Zhu, Changlian
Abstract: Cranial radiotherapy induces endocrine disorders and reproductive abnormalities, particularly in long‐term female cancer survivors, and this might in part be caused by injury to the pituitary gland, but the underlying mechanisms are unknown. The aim of this study was to investigate the influence of cranial irradiation on the pituitary gland and related endocrine function. Female Wistar rat pups on postnatal day 11 were subjected to a single dose of 6 Gy whole‐head irradiation, and hormone levels and organ structure in the reproductive system were examined at 20 weeks after irradiation. We found that brain irradiation reduced cell proliferation and induced persistent inflammation in the pituitary gland. The whole transcriptome analysis of the pituitary gland revealed that apoptosis and inflammation‐related pathways were up‐regulated after irradiation. In addition, irradiation led to significantly decreased levels of the pituitary hormones, growth hormone, adrenocorticotropic hormone, thyroid‐stimulating hormone and the reproductive hormones testosterone and progesterone. To conclude, brain radiation induces reduction of pituitary and reproduction‐related hormone secretion, this may due to reduced cell proliferation and increased pituitary inflammation after irradiation. Our results thus provide additional insight into the molecular mechanisms underlying complications after head irradiation and contribute to the discovery of preventive and therapeutic strategies related to brain injury following irradiation.